Brief Overview of Perovskite Oxide: Synthesis and Its Performance as Oxygen Separator from Air - Silvana Dwi Nurherdiana; Rachmad Ramadhan Yogaswara; Nove Kartika Erliyanti; Atika Nandini; Mutasim Billah; Sintha Soraya Santi; Hamzah Fansuri; Mohd Hafiz Dzarfan Othman; Yuly Kusumawati; Syafsir Akhlus (Nusantara Science and Technology Proceedings)
The aims of this brief overview are providing the knowledge about the physical and chemical properties of perovskite oxides in various synthesis method and the correlation of its performance for separating oxygen from air. Perovskite oxide showed excellent conductor of ion and electron, simultaneously through oxygen lattice in the crystal structure. In the present review, we have presented the detail on the crystal structure and the factor that affect the pseudo-crystal, various synthesis method i.e., solid-state, sol-gel, combustion, and co-precipitation. It has been completed with the discussion of the characteristic and the mechanism of the perovskite to separate oxygen from air